The passenger [large type] - Lutz, Lisa (Center Point Large Print, 2016)
Forty-eight hours after leaving her husband's body at the base of the stairs Tanya Dubois cashes in her credit cards, dyes her hair brown, demands a new name from a shadowy voice over the phone, and flees town. It's not the first time. Blue, a female bartender who recognizes the hunted look in a fugitive's eyes, offers her a place to stay. An uneasy and dangerous alliance is born. Tanya is being chased by a very dark secret-- but can she outrun her past?